EDUCATIONAL PROJECT «PEDAGOGICAL INSIGHT» AS A TECHNOLOGY OF THE FUTURE TEACHERS’ PERSONAL PROFESSIONAL FORMATION - Slushny, Oleg; Khamska, Nelina; Akimova, Olha; Kolomiiets, Alla; Gromov, Ievgen (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article highlights the topicality of the problem of improving the future teachers’ practical training in the process of their professional training in higher pedagogical educational institutions. The authors substantiate the necessity of applying the creative project «Pedagogical Insight: the 21st Century Educational Technologies» in order to secure the innovative component of the students’ professional competence. The authors emphasize on the project activity practical aspects which are based on the use of the pedagogical experience best examples in order to overcome the established stereotypes and search for innovative approaches to educational activities, including participation of the finalists of the «National Teacher Prize Ukraine 2019». The project’s goals, functions, structure, and stages of development have been defined. It has also been emphasized on the importance of the ongoing «Pedagogical Insight» project for the future teachers’ personal and professional formation on the basis of the young teachers’ pedagogical innovations presentation. Those young innovators have reached the pinnacles of pedagogical mastery having developed and implemented their own interpretation of the well-known educational technologies, such as: integrated learning, upturned learning, E-learning, interactive learning, development of emotional intelligence, and others. The effectiveness of the young innovator’s approach to the introduction of the practice oriented teaching of the higher pedagogical institutions’ students on the basis of using the best examples of the «new generation» teachers’ activity has been proved. This effectiveness manifested itself in formation a positive attitude towards their future pedagogical activity; enhancing their professional competence on the basis of mastering the newest pedagogical technologies; understanding the need for lifelong professional training. The article’s aim is to demonstrate the degree of influence of the innovative educational technology «Pedagogical Insight» on the level of motivation of future teachers to personal and professional development. Research methods: studying the advanced pedagogical experience of the young innovative teachers, pedagogical experiment, surveying students and monitoring them in order to determine the degree of influence of participation in the «Pedagogical Insight» project on personal and professional decisions and the beliefs of future teachers regarding the need for constant professional and personal development. Research result: the motivating effect of the innovative technology «Pedagogical Insight» on the adoption by future teachers their ultimate decision on the need for continuous professional and personal development was confirmed.